PROJECT-BASED LEARNING (PjBL) CONTAINS SUSTAINABLE DEVELOPMENT GOALS (SDGs): STUDENTS’ METACOGNITIVE AWARENESS IMPROVEMENT EFFORTS - Andriyatno, Indri; Purwianingsih, Widi; Solihat, Rini; Nurazizah, Widya Eko; Levhan, K.W.A.L. (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
Students' metacognitive awareness can be developed through Project-Based Learning (PjBL) implementation integrating Sustainable Development Goals (SDGs) as a significant aspect of the Kurikulum Merdeka. The purpose of this study is to improve metacognitive awareness through PjBL containing environment change material SDGs. The research method used was a quasi-experiment with a nonequivalent pretest-posttest control group design. The research study covers two groups, i.e., a control group and an experiment group of 36 students of class X of Senior High School respectively. The data-collecting technique used questionnaires and observation. The metacognitive awareness questionnaire adapts the Metacognitive Awareness Inventory (MAI) and a learning implementation observation sheet was used as a research instrument. The data analysis used was an Independent Sample T-Test and N-Gain trial. The Independent Sample T-Test result showed a significant 0.000 difference from the final questionnaire average score between the control and experiment classes. The experiment class students' metacognitive awareness obtained an average score of 84.14 with the highest category and 0.433 of the N-Gain trial score belongs to the medium category. This improvement was supported by the learning implementation result of teachers and students with a very good category. This study was expected to be able to give an effective contribution for teachers to improve the biology learning quality by emphasizing on the students’ metacognitive awareness improvement. The next research shall expand coverage by engaging more schools and considering other factors such as learning methods and students’ learning facility.